2018
DOI: 10.1002/ijc.31317
|View full text |Cite
|
Sign up to set email alerts
|

1,25‐Dihydroxy vitamin D prevents tumorigenesis by inhibiting oxidative stress and inducing tumor cellular senescence in mice

Abstract: Human epidemiological studies suggest that 1,25(OH) D deficiency might increase cancer incidence, but no spontaneous tumors have been reported in mice lacking 1,25(OH) D or deficient in its receptor. In our study, we detected, for the first time, diverse types of spontaneous tumors in l,25(OH) D deficient mice more than 1 year of age. This was associated with increased oxidative stress, cellular senescence and senescence-associated secretory phenotype molecules, such as hepatocyte growth factor, mediated via i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
44
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 50 publications
4
44
0
1
Order By: Relevance
“…VD was regarded as a typical vitamin regulating calcium and phosphorus homeostasis previously . Recently VD is discovered as a highly versatile molecule with emerging roles in immunity, cancer, fatty liver disease, and ALD . A large body of clinical evidence has demonstrated the prevalence and risks of VD deficiency in various chronic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…VD was regarded as a typical vitamin regulating calcium and phosphorus homeostasis previously . Recently VD is discovered as a highly versatile molecule with emerging roles in immunity, cancer, fatty liver disease, and ALD . A large body of clinical evidence has demonstrated the prevalence and risks of VD deficiency in various chronic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…ImageJ software was used to determine areas of Alp and XO staining. For lentiviral infection, viral packaging was performed as described previously (Chen et al, ). Briefly, HEK 293T cells were co‐transfected with lentiviral plasmids (pHAGE‐CMV‐MCS‐IZsGreen), packaging vector psPAX2, and envelope vector pMD2.G by using Lipofectamine 2000 (Invitrogen) according to the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%
“…Alp and XO staining. For lentiviral infection, viral packaging was performed as described previously(Chen et al, 2018).Briefly, HEK 293T cells were co-transfected with lentiviral plasmids(pHAGE-CMV-MCS-IZsGreen), packaging vector psPAX2, and envelope vector pMD2.G by using Lipofectamine 2000 (Invitrogen) according to the manufacturer's instructions. Forty-eight hours after transfection, the supernatants containing lentivirus were harvested for infection in the presence of polybrene (8 µg/ml; Sigma-Aldrich) for 12 hr.…”
mentioning
confidence: 99%
“…In our previous study, we found 1,25(OH) 2 D 3 can enhance the DDIT4 expression in the cultured mice keratinocytes, [6] and it is reported that 1,25(OH) 2 D 3 can suppress some benign or malignant neoplasm growth. [2,4,[10][11][12] So we intended to investigate whether the 1,25(OH) 2 D 3 can also promote the DDIT4 expression and exert its anti-carcinoma effect in human SCC. Gradient concentration 1,25(OH) 2 D 3 of 0, 10 −10 , 10 −9 , 10 −8 , 10 −7 and 10 −6 mol/L was, respectively, used to treat the cultured A431 Figure 3A), IF ( Figure 3B) and quantitative PCR (qPCR) ( Figure 3C) showed all the concentration of 1,25(OH) 2 D 3 significantly promoted the DDIT4 expressions, and it was not a unidirectional dose dependence with the summit at 10 −9 mol/L and the trough at 10 −6 mol/L, which also indicated an optimal concentration of 1,25(OH) 2 D 3 was necessary to exert this biological function (so 10 −9 and 10 −6 mol/L were then taken as the two representative concentrations used in the following experiments).…”
Section: 25(oh) 2 D 3 Enhanced Ddit4 Expression and Activated Autmentioning
confidence: 99%
“…Vitamin D 3 deficiency is reported to associate with the higher risk rates of prostate, breast, colon cancer and polycystic ovary syndrome. [2,4,12] Vitamin D 3 replacement could suppress the tumor cell growth and metastasis through its antiproliferative and pro-apoptotic function, [10,11] and benefit to the malignant tumor control. Recently, 1,25(OH) 2 D 3 also been found to suppress the SCC growth, but its exact mechanism keeps far from fully elucidated.…”
Section: Introductionmentioning
confidence: 99%